A method for measuring the value of scout/reconnaissance - Veit, Clairice T.; Callero, Monti D.; Rand eBooks (Santa Monica, CA : RAND, 1995)
The authors describe a method for developing and using a model to measure the value of scout/reconnaissance to operational performance. The method employs (1) modern measurement techniques to credibly model the human processes involved in situation assessment and operational performance and (2) operator interactive simulation of scout/recon system operations in high-resolution combat models to represent a system's performance on the battlefield. The situation-assessment/operational-effectiveness model is system independent. It can be used to measure the value of any type of reconnaissance system and is relevant to any ground-combat force, organization, or composition. The method fills a critical gap in analytical support for scout/recon system development and acquisition decisionmaking because it provides a quantitative analytical basis for measuring and comparing combat intelligence systems in terms of resulting operational performance. The model applies only to heavy divisions, having been developed from the judgments of intelligence and operations officers about heavy divisions imminently to be engaged in combat with large, modern, enemy armored forces.
"RAND Arroyo Center."
Includes bibliographical references (p. 73-74).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Military reconnaissance -- Computer simulation; Scouts and scouting -- Computer simulation; Electronic books